Concluding remarks - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer, 2020)
This chapter draws the conclusion derived from the book. The key takeaways with regards to the employment of machine learning and different significant parameters towards the performance of team sports, particularly beach soccer and sepak takraw, are summarised and highlighted. The significant implications for the findings to the coaches, team managers, talent scouts, as well as the other relevant stakeholders, are also described. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2020.